Peluang Mengikat Konsumen Melalui Design dan Efesiensi dipandang dari Manfaat Produk untuk Mencapai TOP OF Mind - Azarkasyi, Badarudin (LPPM Universitas Multi Data Palembang, 2024)
The aim of this research is to help market analysis in looking for existing opportunities, so that the products created are very useful. The achievement is to become Top OF Mind with regard to consumers, namely benefits through design and efficiency according to today's needs. The presentation method used uses the Belief-Desire-Intention (BDI) Model by looking at limitations through environmental analysis techniques, consumer attitudes towards the market and business policies of entrepreneurs in producing products towards realization in the field by photographing events and occurrences that are the center of their attention. Research Results Opportunities measured by benefits are still growing high. It can be seen that the hope in the market is still large for entrepreneurs in producing products.